Kepatuhan Cuci Tangan Petugas Non Kesehatan: Literatur Review - Kurnia Aini; Haerawati Idris; M Zulkarnain (Universitas Batanghari Jambi, 2022)
Infection prevention and control is still a problem in health services in Indonesia. Cases such as nosocomial infections, the risk of contracting disease and health problems for medical and non-medical officers that occur as a result of not complying with work procedures, namely washing hands. This study aims to identify and describe the compliance of non-health workers in preventing infection through hand washing. The research method used is literature review, which is looking for articles using data sourced from the internet (google scholar and science direct) using keywords, compliance, hand washing, non-health workers, infection prevention with a time limit of 2019-2022. The search results obtained 8 articles that matched the inclusion criteria, 6 quantitative articles with descriptive studies and 2 articles using experiments which showed that more than half of non-health workers had complied with hand washing which was of course supported by knowledge, availability of facilities and continuous supervision. So this study recommends making a joint commitment to every human resource involved in health services as well as conducting continuous monitoring and providing infrastructure to improve implementation and compliance in washing the hands of non-medical officers in health services.